2019
DOI: 10.2147/dddt.s201453
|View full text |Cite
|
Sign up to set email alerts
|

<p>Solutol<sup>®</sup>HS15+pluronicF127 and Solutol<sup>®</sup>HS15+pluronicL61 mixed micelle systems for oral delivery of genistein</p>

Abstract: Purpose: We aimed to prepare two oral drug delivery systems consisting of polyoxyl 15 hydroxystearate (HS15) with pluronicF127 (F127) and HS15 with pluronicL61 (L61) to overcome the challenges of genistein’s poor oral bioavailability. This provides a good strategy for enhancing the potential value of genistein. Methods: We designed two binary mixed micelle systems employing the organic solvent evaporation method using surfactants (HS15, L61, and F127). Formulations (GEN-F and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…The EE and DLE of GMs prepared with Soluplus® and vitamin E D-α-tocopheryl PEG 1000 succinate were 97:12 ± 2:11% and 3:87 ± 1:26%, respectively [41]. These results indicate that the method adopted in the present study produces GMs with higher DLE and EE.…”
Section: Journal Of Nanomaterialssupporting
confidence: 52%
See 1 more Smart Citation
“…The EE and DLE of GMs prepared with Soluplus® and vitamin E D-α-tocopheryl PEG 1000 succinate were 97:12 ± 2:11% and 3:87 ± 1:26%, respectively [41]. These results indicate that the method adopted in the present study produces GMs with higher DLE and EE.…”
Section: Journal Of Nanomaterialssupporting
confidence: 52%
“…Higher concentrations of Tween 80 produced smaller micelles and higher DLE and EE. GMs were previously synthesized using polyoxyl 15-hydroxystearate combined with Pluronic F127 or Pluronic L61, yielding an EE of 80:79 ± 0:55% and DLE of 1:69 ± 0:24% or an EE of 83:40 ± 1:36% and DLE of 2:26 ± 0:18%, respectively [41].…”
Section: Discussionmentioning
confidence: 99%
“…A micelle system conjugated by stearic acid and Pluronic F68 was prepared by Ashok Kumar Jangid to improve the therapeutic efficacy of baicalin . In addition, the challenge of genistein’s poor oral bioavailability was overcome by a mixed micelle system of polyoxyl-15hydroxystearate (HS15) + Pluronic-F127 (F127) designed by Ding’s group . Many reports have shown that approximately 40% or more of active pharmaceutical ingredients are derived from incompletely water-soluble ingredients, which illustrates the significance of developing a novel surfactant to meet the requirements of new drugs.…”
Section: Introductionmentioning
confidence: 99%